A pilot study expanding participatory epidemiology to explore community perceptions of human and livestock diseases among pastoralists in Turkana County, Kenya - Evan F. Griffith; Job Ronoh Kipkemoi; Jeffrey C. Mariner; Jeanne Coffin-Schmitt; Christopher A. Whittier (CABI, 2024)
Abstract In Kenya, pastoralists grapple with significant health and livelihood challenges due to livestock, zoonotic, and human-specific diseases. These diseases threaten the sustainability of their unique food production system and its considerable economic, nutritional, and ecologic value. Disease control and prevention in arid and semi-arid lands are currently inadequate due to underfunded and ill-adapted health programs coupled with a shortage of personnel. Participatory epidemiology (PE) presents a valuable tool for understanding community perceptions of disease importance and epidemiology, thereby aiding in improving control measures and promoting community involvement in centralized service delivery programs. Yet, the use of PE has focused on livestock and zoonotic diseases, leaving perceptions of human-specific disease and the complex interplay between pastoralists, their livestock, and the rangelands largely unexplored. To address this gap, we utilized PE to achieve three objectives: (1) establish links between human and livestock diseases, (2) determine perceptions of disease priorities, and (3) assess knowledge of disease epidemiology. Our findings indicate that the relationships between human and livestock diseases primarily manifest in two categories: disease symptoms and zoonoses. Disease priorities differed between locations, with no apparent pattern emerging that human or livestock diseases are considered more important. Importance indicators such as prevalence, mortality, morbidity, and spatial/temporal variation were shared across diseases. Diseases perceived as more prevalent and deadly were deemed most consequential, while those seen as less prevalent, less deadly, and exhibiting more spatial/temporal variation were considered important. Our results underscore the added value of including human-specific diseases in PE, which can help improve disease prevention and control initiatives among pastoralists. Human, animal, and environmental health programs and research can leverage and expand upon our approach, combining it with household surveys and other surveillance methods to address health challenges among pastoralists in the drylands of Northern Kenya and beyond.